Consumers Reason For Purchase Of Eco-Friendly Products (Journal of Namibian Studies : History Politics Culture, 2022)
In the field of green marketing consumers attitudes have frequently used in various past studies to predict ecologically conscious consumer behavior and usage of green products. Thus, this research aimed to analyse the consumers reason for purchase of eco-friendly products in Chennai region. Here descriptive research design has been applied. Awareness, attributes, product, price, promotion, eco-friendly, attributes as considered as a independent variable. Purchase intention of consumers is taken as a dependent variable. These variables has been identified based on the previous literature. On the basis of previous literature questionnaire has been constructed to collect the primary data. Using convenience sampling method 182 consumers data has been collected. Further, the data are analyses with help of frequency analysis correlation and regression. The result shows that male, 21-30 years old, unmarried, under graduates respondents purchase the eco-friendly products more on organic shop. The purchase of green food products found to be more among the customers. This also found that awareness, attributes, products, price benefits, promotion, eco-friendly and purchase intention have been related and influence with purchase intention consumers.